Effect of fatigue on kinematics and landing strategies of the ankle during open side cutting in 120-min simulated soccer matchplay - Muhammad Hamdan; Raja Azidin, Raja Mohammed Firhad (Faculty of Sports Science and Recreation, 2025)
The ankle’s capacity to absorb ground reaction forces during dynamic movements is critical for ACL injury prevention, yet the biomechanical changes in ankle kinematics and foot strike patterns induced by soccer-specific fatigue during high-risk maneuvers like side-cutting remain poorly understood, hindering the development of holistic injury risk assessment and mitigation strategies. The purpose of this study was to investigate the effects of fatigue on sagittal plane ankle angles during initial contact of side cutting tasks and observe the landing strategies recruited during such tasks in a simulated soccer match-play. Eighteen (n = 18) male, recreational participants (age: 23.1 ± 4.7, height: 1.7 ± 0.1 m; body mass: 70.6 ± 10.0 kg) volunteered for the study. Participants completed 120 minutes of simulated soccer match-play with a 15-minute passive half-time rest period interceding at the 45-minute mark and another 5-minute rest period at the end of 90 minutes of simulated soccer match-play and performed 5 successful trials of side cutting for both dominant and non-dominant limbs at all time points (time: 0 min, 45 min, 60 min, 105 min, 110 min, 125 min, 140 min) during the simulation. A 2 (limb: dominant, non-dominant) × 7 (time: 0 min, 45 min, 60 min, 105 min, 110 min, 125 min, 140 min) mixed within-between analysis of variance was conducted for each dependent variable while the occurrence for different landing strategies was also recorded. There was a significant main effect of time on the ankle angles (F3.493, 104.803 =3.521, p = 0.013, partial η2 = 0.105). However, no significant interaction effect was observed (F3.349, 104.803 = 0.419, p = 0.769, partial η2 = 0.014), suggesting that limb dominance does not play a role in the changes occurring in the ankle angles over time. The probabilities for rearfoot landings appear to increase over time to over 0.75, whereas forefoot landing probabilities appear to drop to below 0.20. This pattern could introduce multiplanar challenges to the anterior cruciate ligament, aligning the structure awkwardly and increasing the forces acting on the ligament. Researchers and practitioners may consider exploring the efficacy of targeted interventions to offset the effects of fatigue on landing strategies and kinematics among soccer players.